Patterns and predictors of adherence to follow-up health guidance invitations in a general health check-up program in Japan: A cohort study with an employer-sponsored insurer database. - Yuichiro Mori; Kunihiro Matsushita; Kosuke Inoue; Shingo Fukuma (PLoS ONE, 2023)
Background Japan has conducted a nationwide annual health check-up program since 2008, focusing on metabolic syndrome and subsequent health guidance in individuals at high risk for cardiovascular disease. However, the adherence rate to health guidance invitations was assumed to be low in previous reports. Therefore, this study aimed to characterize adherence patterns in the program and identify major predictors of adherence to health guidance invitations. Methods We studied 186,316 adults (aged 40-74 years) who were included in a nationwide employer-sponsored insurer's database in Japan at the beginning of the fiscal year 2017. We first described adherence to health check-ups, the proportion of individuals with high cardiovascular risk, and adherence to health guidance invitations. Predictors of adherence to the invitation were then identified among eligible high-risk individuals. Results In 2017, 71.7% of the study population (n = 133,573) underwent health check-ups, among whom 23.2% (n = 30,979) were invited for health guidance because of their high cardiovascular risk. Among those individuals, 35.2% (n = 10,614) received health guidance. Predictors of improved adherence to health guidance invitation were older age, more concerning blood pressure or laboratory data results, and self-reported motivation for a lifestyle change. Conclusion Though 70% of eligible adults attended Japan's annual cardiovascular risk check-ups, only 35% of individuals with high cardiovascular risk adhered to health guidance invitations. Future policy reforms to improve adherence to this program should target younger individuals and those with mild stages of hypertension, diabetes, or dyslipidemia.